Radioguided occult lesion localisation using iodine‐125 seeds ('ROLLIS') for removal of impalpable breast lesions: First Australian experience. Issue 4 (14th April 2015) - Taylor, Donna B.; Bourke, Anita G.; Westcott, Eliza; Burrage, John; Latham, Bruce; Riley, Paul; Ballal, Helen; Kamyab, Roshi; Frost, Felicity; Dissanayake, Deepthi; Landman, Joanne; Phillips, Michael; et al.
Abstract: Introduction: Approximately one‐third of breast cancers are impalpable and require pre‐operative image‐guided localisation. Hook‐wire localisation (HWL) is commonly used but has several disadvantages. Use of a low‐activity radioactive iodine‐125 seed is a promising alternative technique used in the USA and the Netherlands. This pilot study describes the first use of this in Australia. Methods: In this prospective pilot study, 21 participants with biopsy‐proven breast cancer underwent radioguided occult lesion localisation using iodine‐125 seed(s) (ROLLIS) with insertion of a hook‐wire for back up. Sentinel node biopsy was performed where indicated. Ease of hook‐wire and seed insertion, duration of the procedure, dependence on the seed versus hook‐wire during surgery, lesion location within the specimen, histopathology including size of radial margins, the ease of seed retrieval in pathology, and safe return of seeds for disposal were documented. Radiation dosimetry of staff was performed. Results: All seeds were placed within 3.5 mm of the lesion. All lesions and seeds were removed. One participant needed re‐excision for involved margins. Radiologists and surgeons both preferred ROLLIS. Surgeons were able to depend on the seed for localisation in all but one case. Sentinel node biopsy was successfully performed when required. Pathologists found seed retrieval quick and easy, with no detrimental effect on tissue processing. No radiation doses measurably above background were received by staff. Conclusion: ROLLIS is an easily learnt, safe and effective alternative technique to standard HWL.